Periostin as a promising target of therapeutical intervention for colorectal cancer - Song, Li Na; Li, Ling Xia; Shi, Qing Hong; Fang, Ling; Sun, Li; Zhao, Hai Feng; Liu, Ning; Li, Hong Jun; He, Cheng Yan (Bangladesh Journal of Pharmacology, 2014)
The expression of periostin in the tissue of colorectal cancer patients and its correlation with clinical features were studied. Periostin expression was 4 fold up-regulated in cancer tissues compared to adjacent non-cancerous tissues. Serum levels of periostin in patients were significantly elevated to 32.6 ± 10.8 ng/mL vs 20.4 ± 11.1 ng/mL in healthy volunteers. Higher preoperative serum periostin levels in patients were closely related to advanced-stage disease (stage III/IV), distant and lymph nodes metastasis. High level of periostin expression was detected in the SW480 human colon carcinoma cells, and could be down-regulated by small interfering RNAs (siRNA). The siRNA-mediated knockdown of periostin arrested the cell cycle at G0/G1 phase and induced apoptotic cell death in the SW480 cells. In conclusion, periostin is a promising prognostic and therapeutic target for colorectal cancer.